2015
DOI: 10.1016/j.ccell.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-CoA Synthetase 2 Promotes Acetate Utilization and Maintains Cancer Cell Growth under Metabolic Stress

Abstract: SummaryA functional genomics study revealed that the activity of acetyl-CoA synthetase 2 (ACSS2) contributes to cancer cell growth under low-oxygen and lipid-depleted conditions. Comparative metabolomics and lipidomics demonstrated that acetate is used as a nutritional source by cancer cells in an ACSS2-dependent manner, and supplied a significant fraction of the carbon within the fatty acid and phospholipid pools. ACSS2 expression is upregulated under metabolically stressed conditions and ACSS2 silencing redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
602
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(657 citation statements)
references
References 64 publications
24
602
5
1
Order By: Relevance
“…5g and 5h) and isotope tracing with deuterated acetaldehyde confirmed that ACLY knockdown cells exhibited increased acetate utilization which could be further increased by limiting nutrient availability during serum starvation (Fig. 5i), which is consistent with previous findings 10,34 . Thus these experiments confirm that de novo pyruvate-derived acetate production can have critical functional roles in supporting acetyl-CoA metabolism.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…5g and 5h) and isotope tracing with deuterated acetaldehyde confirmed that ACLY knockdown cells exhibited increased acetate utilization which could be further increased by limiting nutrient availability during serum starvation (Fig. 5i), which is consistent with previous findings 10,34 . Thus these experiments confirm that de novo pyruvate-derived acetate production can have critical functional roles in supporting acetyl-CoA metabolism.…”
Section: Resultssupporting
confidence: 90%
“…The dependence on acetate to supply both nucleocytosolic and mitochondrial acetyl-CoA pools has been identified in multiple cell types, including cancer cells, T cells, and neurons [8][9][10]13,14 . Our study provides evidence for a glucose-derived overflow pathway for acetate metabolism that occurs in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not include possible direct contributions from unlabeled glutamine (i.e. through cytosolic reductive carboxylation by isocitrate dehydrogenase IDH1 or mitochondrial IDH2) and potentially from the cytosolic acetyl-CoA synthetase 2 (ACSS2) reaction (50).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Although the initial focus of this field has been aerobic glycolysis (the Warburg effect), 6 increasing evidence points to a complex landscape of tumor metabolic circuitries beyond aerobic glycolysis, including varied contribution of mitochondria to tumor metabolism as well as heterogeneity in fuel utilization pathways. [7][8][9][10][11][12] Diffuse large B-cell lymphomas (DLBCLs) are a genetically heterogeneous group of tumors that can be classified into distinct molecular subtypes based on gene expression profiles. The cell-of-origin (COO) classification defined DLBCL subsets that shared certain components of their RNA profiles with normal germinal center B cells (GCBs) or in vitroactivated B cells (ABCs), and a third undefined subset designated 'type 3'.…”
mentioning
confidence: 99%